A New Step-Up Switched-Capacitor Voltage Balancing Converter (International Journal of Innovative Research in Engineering & Management, 2022)
The new step-up capacitor grid is connected  to the solar photovoltaic (PV) having a voltage balancing  converters. It’s suitable for Neutral-Point-clamped (NPC)  Multilevel Inverter (MI). To balance the capacitor DC link  voltage effectively we've got to use switched capacitors. By  using balancing converter, we will enlarge the higher levels  and also by boosting input voltage we are able to see the  upper levels of voltage without using magnetic components.  This attribute allows operating the input and output voltage by  self-balancing. The balancing converter for NPC multilevel  inverter-based solar PV system is operated by using vector  scheme control. PV system incorporates a Maximum power  point Tracking (MPPT) and it's executed in Matlab power  system. The output of the simulation result topology can  successfully balance the DC voltage and excess power from  grid. The injected power within the grid can vary the solar  light with active performances.
Keywords: voltage balancing converter; switched capacitors; Matlab power system